Piezoresistive pressure sensor based on conjugated polymer framework for pedometer and smart tactile glove applications - Gupta, Neelam; Adepu, Vivek; Tathacharya, Manav; Siraj, Sohel; Pal, Subhradeep; Sahatiya, Parikshit; Kuila, Biplab Kumar (Sensors and actuators. A. Physical., 2023)
Conjugated polymer frameworks which are generally less solution processable are rarely explored for flexible pressure sensor application in spite of their great potentiality that arises from three dimensional network structure, excellent conductivity, thermal stability and porosity. The report demonstrates the development of conjugated polymer framework (CPF) based flexible piezoresistive sensor and further utilization of the same for real time Pedometer and Smart Tactile Glove applications. CPF was deposited onto the cellulose paper by vacuum filtration method followed by encapsulation with PDMS to improve the flexibility and avoid the interaction of CPF with the ambient. The sensitivity of the fabricated CPF based pressure sensor was observed to be 2.92 kPa−1 with high repeatability and reliability. The transduction mechanism of the CPF based pressure sensor can be attributed to the increase in the contact areas between individual nanostructures when pressure applied and increase the current flow. The fabricated CPF-pressure sensor was further demonstrated for real time applications such as Pedometer which counts the number of steps and also Smart Tactile Glove which finds potential applications towards human machine interface. Dedicated Android applications are developed wherein the analyzed data is displayed to the user with Bluetooth as the medium of data transfer. Successful demonstration of organic materials for the use of physical sensor is a major step ahead in the field of organic electronics and opens up new avenues of research towards low-cost physical sensors for personal healthcare monitoring. [Display omitted] •Flexible piezoresistive pressure sensor from conjugated polymer framework (CPF) was proposed and experimentally demonstrated.•The pressure sensor was fabricated by depositing CPF onto the cellulose paper followed by encapsulation with PDMS.•The sensitivity of the fabricated pressure sensor was observed to be 3.01 KPa-1 with high repeatability and reliability.•The senor was further utilized for real time Pedometer and Smart Tactile Glove applications.•Dedicated Android applications are developed wherein data is displayed to user with Bluetooth as medium of data transfer.